BAZNAS RI and the Madrasah Layak Belajar Program: Evaluating Social Intervention in Educational Infrastructure and Student Learning - M. Saddam Kiramuddin Al-Wathani Al-Wathani (Postgraduate Program Magister Pendidikan Agama Islam, 2026)
This study aims to analyze the implementation of the Madrasah Layak Belajar (MLB) Program by BAZNAS RI in supporting the learning process in madrasahs, with a focus on infrastructure conditions and their psychological implications for students. The research employed a descriptive qualitative approach, with data collected through non-participant observation and semi-structured interviews at one of the program recipient madrasahs, namely MI Al-Muslimun NW. Participants included the madrasah principal, teachers, and students. The results indicate that the program successfully improved the basic infrastructure conditions of the madrasah, such as classrooms, lighting, ventilation, and sanitation, making them more feasible and conducive to learning. Infrastructure improvements positively impacted teaching effectiveness and enhanced student motivation, comfort, discipline, and engagement in the learning process. From an educational psychology perspective, adequate physical environments function as external supporting factors that strengthen students' emotional comfort and readiness to learn. This study concludes that infrastructure-based interventions through Islamic philanthropic programs such as MLB play a strategic role in improving the quality of madrasah education, both academically and psychologically. Program sustainability through facility maintenance and stakeholder collaboration is essential to maintain the positive impacts achieved.